Strategi Transformasi Digital: Inovasi Program Tuka Tuku Purbalingga - Latifah, Nur Laela Dian; Adzam, Muh.; Vidiastuti, Dwi Putri (Research and Development Agency Ministry of Home Affairs, 2024)
The shift towards digitalization has become a crucial factor in advancing various sectors of life in this modern era. One sector significantly affected is local governance, with the Tuka Tuku Purbalingga Program serving as a tangible example of digital innovation implementation to enhance public services and bolster the local economy. Faced with the low interest of Micro, Small, and Medium Enterprises (MSMEs) in this program, this research aims to identify strategies needed to introduce Tuka Tuku as a digital platform for selling products to MSMEs in Purbalingga. Through an exploratory qualitative approach, where qualitative research is employed to investigate phenomena in the field, purposive sampling method is used to select informants for this study. The analysis employed is Interactive Analysis involving data collection, reduction, presentation, and conclusion drawing. The research findings indicate that out of the three digital transformation strategies identified according to Westerman’s theory-customer experience, operational processes, and business model - not all have been fully implemented in the Tuka Tuku Purbalingga Program. Overall, this research concludes that the digital transformation process among MSMEs in Purbalingga is still in its early stages. Despite some positive steps taken, there are still several challenges to be addressed. Digital transformation is not merely about technology utilization but also involves changes in mindset, business models, and the enhancement of required skills.